A Study on Potential Progressive Collapse Responses of Cable-Stayed Bridges. Issue 4 (April 2013) - Aoki, Yukari; Valipour, Hamid; Samali, Bijan; Saleh, Ali
In this paper, a finite element (FE) model for a cable-stayed bridge designed according to Australian standards is developed and analysed statically and dynamically with and without geometrical nonlinearities. The dynamic amplification factor ( DAF ) and demand-to-capacity ratio ( DCR ) in different structural components including cables, towers and the deck are calculated and it is shown that DCR usually remains below one (no material nonlinearity occurs) in the scenarios studied for the bridge under investigation, however, DAF can take values larger than two. Moreover, effects of location, duration and number of cable(s) loss as well as effect of damping level on the progressive collapse resistance of the bridge are studied and importance of each factor on the potential progressive collapse response of the bridgeis investigated.